Model-Eliciting Activities on Students' Mathematical Literacy by Reviewing Differences in Self-Regulated Learning - Ika Nada Fajriyah; Mohammad Faizal Amir; Mahardika Darmawan Kusuma Wardana; Mohd Nazri Abdul Rahman (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractThe mathematical literacy of students is still relatively low. However, it remains a goal and a necessity to develop mathematical literacy as a fundamental skill for solving problems in various contexts, particularly in formulating, employing, and interpreting mathematics. Previous studies have proven that model-eliciting activities effectively enhance mathematical literacy. On the other hand, mathematical literacy is influenced by differences in self-regulated learning. Therefore, this study answers whether implementing model-eliciting activities regarding self-regulated learning differences affects students' mathematical literacy. This study employed a quasi-experimental non-equivalent pretest and posttest design that involved 55 fourth-grade primary students. Data collection used a mathematical literacy test and a self-regulated learning questionnaire. The levels of self-regulated learning were categorised as low, medium, and high. The data analysis was a two-way analysis of variance test followed by the Tukey test. The study showed that implementing model-eliciting activities by considering differences in self-regulated learning affected students' mathematical literacy. Another finding is that students with high self-regulated learning are better at mathematical literacy than those with low self-regulated learning.Keywords: model-eliciting activities, mathematical literacy, self-regulated learning. AbstrakLiterasi matematika siswa masih tergolong rendah, namun sampai saat ini masih menjadi tujuan dan kebutuhan sebagai keterampilan fundamental untuk menyelesaikan masalah dalam berbagai konteks khususnya dalam hal merumuskan, menggunakan, dan menafsirkan matematika. Peneliti-peneliti sebelumnya telah membuktikan model-eliciting activities efektif untuk meningkatkan literasi matematika. Disisi lain, literasi matematika dipengaruhi oleh perbedaan self-regulated learning. Oleh karena itu, penelitian menjawab rumusan masalah mengenai apakah implementasi model-eliciting activities dengan memperhatikan perbedaan self-regulated learning berpengaruh terhadap literasi matematika siswa. Penelitian ini menggunakan quasi eksperimental non-equivalent pretest dan posttest desain dengan melibatkan 55 siswa kelas empat sekolah dasar. Pengumpulan data menggunakan tes literasi matematika dan kuisioner self-regulated learning. Perbedaan tingkat self-regulated learning dikategorikan sebagai rendah, sedang, dan tinggi. Analisis data yang digunakan adalah uji analisis varians dua arah dan dilanjutkan uji Tukey. Temuan penelitian menunjukkan implementasi model-eliciting activities dengan memperhatikan perbedaan self-regulated learning berpengaruh terhadap literasi matematika siswa. Temuan lainnya adalah siswa yang memiliki self-regulated learning tinggi lebih baik dalam literasi matematika dibanding siswa yang memiliki self-regulated learning rendah.Keywords: model-eliciting activities, literasi matematika, self-regulated learning.